Safety of Antarctic krill (Euphausia superba) as food source: its initial fluoride toxicity study - ZHANG,Hai-Yan; CAO,Ming-Xiu; FODJO,Essy Kouadio; KONG,Cong; CAI,You-Qiong; SHEN,Xiao-Sheng; CHEN,Xue-Zhong (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2018)
Abstract Antarctic Krill, rich in many nutrients, is supposed to be one of the strategic food sources. However, it is not acceptable for direct consumption as traditional food, as its high content of fluoride is harmful to adults and children. Therefore, the safety of fluoride residue in Antarctic krill for food production should be investigated. In this research, the fluoride toxicity in Antarctic Krill was evaluated through mice feeding experiment. Their body weight was found not to be influenced by fluoride. However, dental fluorosis was observed in the krill group and the NaF group. Fluoride content in liver, kidney, urine, and bones are significantly different (P<0.05) among these three groups, which amount to plateau during the first ten days of feeding, except the fluoride in bone which keeps increasing all through the experimental time. Furthermore, less amount of fluoride was determined in the krill group compared with the amount in NaF group, even if they have the same concentration of fluoride. Besides, lesions in livers, kidneys and bones of the two experimental groups were observed through histopathological studies.